Pengaruh Motivasi, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kinerja Pegawai Non-Medis pada Rumah Sakit Pelabuhan Palembang - Mardiana Puspasari; Wani Fitriah (Jurnal Bisnis, Manajemen, dan Ekonomi, 2020)
This research aims: (1) to find impact of motivation, work discipline, work environment simultaneously to non-medical employees performance on Palembang Port Hospital, and (2) to find impact of motivation, work discipline, work environment partially to non-medical employees performance on Palembang Port Hospital. Design used in this research is regressional. Variables used are four variables, those are independent variables which Work Motivation (X1), Work Discipline (X2), and Work Environment (X3), and also dependent variables is Non-Medical Employees Performance (Y). Population in this research as much 107 persons. All the population used to sample. The analytical tool used is multiple linear regression. According to the research result, find: (1) Work motivation, work discipline, and work environment simultaneously have positive and significant effects to non-medical employees performance on Palembang Port Hospital, (2) Work motivation have positive and significant effects to non-medical employees performance on Palembang Port Hospital, (3) Work discipline have positive and significant effects to non-medical employees performance on Palembang Port Hospital, and (4) Work environment have positive and significant effects to non-medical employees performance on Palembang Port Hospital